Neglected and Underutilized Species in the perspective of Food and Nutritional Security promotion in Brazil (Research, Society and Development, 2021)
The diet of the world’s population has been increasingly characterized by the predominance of industrialized foods and low consumption of vegetables, including native plants. These species are rich in nutrients and show a potential to diversify diets, possibly contributing to the promotion of food security of many Brazilian families. In this sense, this work aims to systematize knowledge about the relevance of inserting Neglected and Underutilized Species (NUS) in the Brazilian population’s diet, in the perspective of Food and Nutritional Security (FNS) promotion. For this purpose, a narrative review was conducted, by means of consultations in databases and websites of scientific research, covering the following contents: 1. the current Brazilian dietary pattern; 2. Neglected and Underutilized Species and nutritional contributions; and 3. Neglected and Underutilized Species in promoting FNS. Studies point out that the Brazilian population has been replacing traditional foods with processed foods, which is a risk factor for the development of chronic non-communicable diseases. Additionally, studies reveal that NUS are rich in nutrients, can play an important role in perpetuating healthier eating habits, and the incorporation of these vegetables in national food and nutrition policies is an excellent strategy in the perspective of promoting FNS. In the face of the findings, it has been concluded that appreciation of NUS and stimulation of the consumption of these vegetables have become important for the promotion of biodiversity and sustainability, strengthening governmental actions for food security in the country.